Glosa do postanowienia Naczelnego Sądu Administracyjnego z 6 lipca 2016 r., sygn. akt. I OSK 1516/16 - Reczek, Kamil (Studia Prawa Publicznego, 2022)
In its judgment of 6 July 2016, I OSK 1516/16, the Supreme Administrative Court ruled that proceedings initiated by the complaint referred in Art. 68 of the Act on Vehicle Drivers by a person subjected to a driving test is an administrative proceeding for the invalidation of the state driving test, which, pursuant to Art. 72 Clause 1 of the Act on Vehicle Drivers, should be concluded by an administrative decision. This means that the test taker has the right to challenge the conduct of a driving test in jurisdictional administrative proceedings, because he or she is entitled to initiate proceedings for its invalidation. It is a new, precedent-setting and favorable view for the examinee. Although it is also socially significant, because it concerns a common matter, it is impossible to agree with it, because in accordance with the intention of the legislator, the examinee is not entitled to initiate such proceedings. He or she only can signal in the complaint procedure specified in Section VIII of the Act of 14 June 1960 the Code of Administrative Procedure to the voivodeship marshal the need to initiate such proceedings ex officio.